Soroprevalência, distribuição espacial e fatores associados à infecção por Leishmania spp. em cães da área urbana do município de Rondonópolis, Mato Grosso, Brasil (2016-2017) : estudo transversal - Carvalho, Amanda Gabriela de (2018)
This study evaluated the seroprevalence, spatial distribution, and associated factors related to the infection by Leishmania spp. in dogs from the urban area of Rondonópolis. A cross-sectional study was performed between October 2016 and February 2017. A representative sample of households with dogs was employed (n = 416). The sampling process was conducted proportionally in 25 spatial regions previously defined by the SKATER algorithm (Spatial ‘K’luster Analysis by Tree Edge Removal), which employed variables from the Demographic Census (2010). These regions were composed internally by contiguous census tracts with socioeconomic and environmental similarities. Posteriorly, home visits were conducted for: (i) blood collection in all dogs, (ii) georeferencing with a GPS navigation device, and (iii) interview with the owner regarding socioeconomic and environmental aspects, knowledge about visceral leishmaniasis (VL), care given as well as dog’s physical and behavioral characteristics. The canine infection by Leishmania spp. was defined by double positivity in a rapid immunochromatographic test and enzyme immunoassay. The distribution of the households with positive and negative animals was analyzed using the kernel density estimation (KDE), and scan statistics to detect clusters of high or low prevalence. In parallel, all the autochthonous human VL cases reported in the municipality between 2014 and 2016, was georeferenced. A total of 602 animals distributed in 405 households were evaluated, of which 115 were seropositive in both techniques. The overall seroprevalence of the canine infection by Leishmania spp. was 19.2% [95%CI = (16.1%; 22.3%)], and widely varied among the evaluated regions. Considering the sampled households, 24.9% [95%CI = (20.7%; 29.2%)] had at least one infected dog. KDE demonstrated that positives households were concentrated in the peripheral areas of the city. On the other hand, in the central area of the city, scan statistics detected a spatial cluster with significant low prevalence of the infection (relative risk = 0.37; p = 0.04). It were reported 30 cases of human VL in Rondonópolis along the three years prior to the present study, which were distributed mainly outside the cluster with low prevalence of canine infection. The factors associated with the infection by Leishmania spp. were: social class [OR = 2.0, 95%CI = (1.2;3.2)]; acerola tree in the yard [OR = 2.2, 95%CI = (1.2;4.1)]; number of dogs in the household [OR = 2.0, 95%CI = (1.3;3.3)]; breeding of horses and cattle [OR = 12.0; 95%CI = (1.9;73.6)]; existence of homes with backyards nearby [OR = 4.0; 95%CI = (1.3;12.2)]; apparent symptoms suggestive of CVL [OR = 10.6; 95%CI = (5.8;19.4)]; dog breeding in the yard during the day [OR = 4.8, 95%CI = (1.1;21.4)]; absence of cleanliness of the place where the dog sleeps [OR = 1.9, 95%CI = (1.1;3.2)]. By the first time in Rondonópolis it was demonstrated a high seroprevalence of the infection by Leishmania spp. in animals from diversified socioeconomic and environmental urban contexts, which was basically distributed on the periphery, especially in those areas with reporting of human VL cases. In addition, the associated factors were closely related to socioeconomic and environmental characteristics.